First results of the preoperative accelerated partial breast irradiation (PAPBI) trial. Issue 3 (March 2015) - van der Leij, Femke; Bosma, Sophie C.J.; van de Vijver, Marc J.; Wesseling, Jelle; Vreeswijk, Sandra; Rivera, Sofia; Bourgier, Celine; Garbay, Jean-Rémi; Foukakis, Theodoros; Lekberg, Tobias; van den Bongard, Desiree H.J.G.D.; van Vliet-Vroegindeweij, Corine; et al.
Abstract Background and purpose The aim of this study is to assess the toxicity and cosmetic outcome of preoperative accelerated partial breast irradiation (PAPBI) for breast cancer patients with low risk on local recurrence. Material and methods Women aged ⩾60 years with an invasive, unifocal ⩽3 cm on MRI, (non-lobular) adenocarcinoma of the breast and a negative sentinel node received PAPBI (40 Gray in 10 fractions over 2 weeks). Six weeks after radiotherapy a wide local excision was performed. Results 70 patients with a median follow-up of 23 months (3–44 months) were evaluated. The overall postoperative infection rate was 11%. At 1, 2 and 3 years of follow-up respectively 89%, 98% and 100% of patients had no or mild induration-fibrosis. Fibrosis was only found in a small volume of the breast. The global cosmetic outcome was good to excellent in 77% at 6 months to 100% at 3 years. Two patients developed a local recurrence. Conclusion Our first results show limited fibrosis in a small volume and good to excellent cosmetic outcome. In selected patients, preoperative radiotherapy appears to be a good option for breast conserving therapy.